Direct stent puncture technique for recanalization of superficial femoral artery in-stent occlusion - Kurtuluş Karaüzüm; İrem Karaüzüm; Ulaş Bildirici (KARE Publishing, 2019)
In-stent restenosis and occlusion are common, well-known complications of superficial femoral artery (SFA) interventions. The treatment options in such cases are re-intervention or surgery. A percutaneous antegrade approach is an effective and safe method to perform SFA stent restenosis or occlusion treatment. If an antegrade intervention fails, a retrograde transpopliteal approach may be an alternative. However, in some patients who are admitted with acute leg ischemia there is no distal vessel flow. This condition can result in the need for extremity amputation. Presently described is a case in which a direct stent puncture technique was applied to recanalize the SFA in-stent occlusion after an initially unsuccessful antegrade intervention.